Exploring the Role of Mental Preparedness and Emotional Competence in Nurturing Academic Success among Students in the Post-Pandemic Instructional Landscape - Darryl H. Faciolan (RIRAI Publisher, 2024)
This study examines the relationship between students' mental preparedness, emotional competence, and their academic success in the context of the reintroduction of full in-person instructional setup after a hiatus of almost three years. Using a descriptive correlational research design, the study aimed to provide a comprehensive understanding of these variables. The Grade 11 students from Langgal National High School were selected as the respondents. The findings highlight the significant influence of mental preparedness on students' performance in academic activities, underscoring the importance of being mentally prepared to address learning challenges, especially in the context of the pandemic. Additionally, the study reveals a moderate association between the level of emotional competence and academic success, emphasizing its role as a personal resource in adapting to the learning environment. Overall, the results suggest that students' mental preparedness and emotional competence during full in-person classes significantly contribute to their likelihood of achieving academic success.